ANALISIS HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN PASIEN DI PUSKESMAS CILACAP TENGAH I - Cindy Yuanita; Maesaroh Maesaroh; Budi Puspo Priyadi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Health is an important aspect of the development of the country. The government was realizing the first level of health services then formed the Puskesmas. Patients want satisfaction through improving the quality of health services. In 2015-2019 there was a decrease in the number of visitors to the Puskesmas Cilacap Tengah I. It was due to the lack of service quality, unfriendly staff, and doctors who were not clear in providing information related to patients' illnesses. This study aims to analyze the relationship between service quality and patient satisfaction at Puskesmas Cilacap Tengah I. This study uses a quantitative approach. The sample of this research is 99 using the accidental sampling technique. The analysis technique used the Kendall b test and the Kendall W test. The results showed that reliability, responsiveness, empathy, and the physical evidence had a positive and significant relationship to satisfaction, while assurance had a positive but not significant relationship. Simultaneously reliability, responsiveness, physical assurance, empathy, and evidence have a relationship with patient satisfaction